Guinea-Bissau : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility and Financing Assurances Review: Staff Report; Joint IMF/World Bank Debt Sustainability Analysis; Informational Annex; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2011)
A confluence of developments is creating a more favorable economic situation for Guinea-Bissau. The country has moved away from debt distress with the debt relief granted after the Highly Indebted Poor Countries completion point last year. Fiscal sustainability has improved considerably through expenditure control and substantial increases in revenue. For the first time, the 2012 budget envisages sufficient fiscal revenue to cover current spending. The immediate challenge is to maintain fiscal prudence, modernize the public administration and defense and security sectors, and create space for private sector development.